Karakteristik Gelombang Ultrasonik pada Nanas (Ananas comosus (L.) Merr.) dengan Tiga Tingkat Kematangan - Wendianing Putri Luketsi; I Wayan Budiastra; Usman Ahmad (PERTETA, 2017)
AbstractCurrently, determination of quality of fresh pineapple is still subjective by visual judgement based on its color, resulting high variation of ripeness judgement and often does not represent its internal quality. Therefore, we need a non-destructive method that could accurately evaluate internal quality of pineapple, one of which is ultrasonic method. The purposes of this study were to determine the characteristic ofultrasonic transmission (velocity, attenuation coefficient) and physicochemical properties in pineapples and to examine ultrasonic transmission correlation with their physicochemical properties. Pineapple with three ripeness were harvested. Ultrasonic transmission characteristic in pineapples at a frequency of 50 KHz were measured, then followed by measurement of its physicochemical properties (firmness, density, total soluble solid, and total acid). The result showed that the velocity of ultrasonic transmission in pineapples at three ripeness levels were significantly different, ranged between 172.51 to 210.06 m/s. The riper the pineapple,the lower the ultrasonic transmission velocity. The ultrasonic attenuation coefficient in pineapples ranged from 4.09 – 5.14 dB/m. Ultrasonic attenuation coefficient increases as pineapple is riper. Both ultrasonic velocity and attenuation coefficient have linear correlations with firmness.AbstrakPenentuan kualitas buah nanas segar saat ini masih bersifat subyektif berdasarkan warna, sehingga hasil pemutuannya sangat beragam dan tidak sesuai dengan mutu internal. Oleh karena itu diperlukan metode nondestruktif yang mampu mengevaluasi mutu internal nanas, salah satunya adalah metode ultrasonik. Tujuan penelitian ini adalah menentukan karakteristik transmisi gelombang ultrasonik (kecepatan, koefisien atenuasi) dan sifat fisikokimia nanas serta mengkaji hubungan antara karakteristik transmisi gelombangultrasonik dengan sifat fisikokimia buah nanas. Buah nanas dengan tiga tingkat kematangan dipanen , kemudian langsung dilakukan pengukuran sifat transmisi gelombang ultrasonik pada frekuensi 50 kHz, dilanjutkan dengan pengukuran sifat fisikokimia (kekerasan, densitas, total padatan terlarut, dan total asam). Hasil penelitian menunjukkan kecepatan gelombang ultrasonik buah nanas pada tiga tingkat kematangan berbeda nyata, berkisar antara 172.51 – 210.06 m/s. Semakin matang buah nanas, kecepatan gelombangultrasonik semakin menurun. Sedangkan koefisien atenuasi berkisar antara 4.09 – 5.14 dB/m. Koefisien atenuasi semakin meningkat dengan semakin matangnya nanas. Kecepatan dan koefisien atenuasi gelombang ultrasonik mempunyai korelasi linier dengan kekerasan nanas.